Wet-spun weavable MXene/sodium alginate evaporator for efficient solar-driven water purification and concurrent power generation - Haofeng Liu; Jincheng Zhang; Shenao Wang; Weilin Xu; Huawang Zhao; Dongmao Ye; Hongjun Yang (Desalination, 2026)

Machine learning-assisted sensor array based on single trimetallic nanozyme with multienzyme-like activities for rapid and intelligent identification of multiple metal ions - Yuxuan Shen; Xincheng Xie; Chunmeng Deng; Xiaolei Geng; Yanfei Yang; Yu Luan; Yanmin Zou; Kun Zeng; Qiu Shen; Dali Wei; Zhen Zhang; Hongjun Zhao (Analytica Chimica Acta, 2026)

Tire wear particles in the environment: A critical review on key challenges and future perspectives in fate, risk, and mitigation - Niling Zou; Hongjun Xiao; Gaoju Zou; Dehua Du; Zhen Liu; Shixin Zhang; Jiayue Zhu; Fan Yang; Kaifeng Wang; Anke Du; Yao Chen (Journal of Water Process Engineering, 2026)

When and where do university-related travelers use ride-hailing? Evidence from 75 universities in Tianjin, China - Xinwei Ma; Jichi Zhao; Weijie Yu; Hongjun Cui; Yang Liu (Journal of Transport Geography, 2026)

Estimating daily evapotranspiration from remotely sensed instantaneous observations with surface flux equilibrium (SFE) theory and maximum entropy production (MEP) principle - Xin Pan; Zhanchuan Wang; Jinlong Shi; Yuanbo Liu; Zi Yang; Xu Ding; Suyi Liu; Hongjun Zhu; Congbao Zhu; Shile Yang; Yingbao Yang (Journal of Hydrology, 2026)

Interfacial energy homogenization enables β-phase transition and high piezoactivity in MOF/PVDF membrane for sustainable pollutant degradation - Zi Yang; Miaomiao Tian; Cheng Chen; Zhiyu Zhao; Libo Zhao; Jiujing Xu; Wei Yu; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Associations of prenatal PFAS exposure with offspring neurobehavioral outcomes by maternal folate supplementation and cord blood 5-MTHF levels: a prospective birth cohort study - Susu Wang; Chunping Hu; Xin Liang; Lijun He; Hongjun Shi; Shuhua Yang; Ji Bian; Qianlong Zhang; Junjie Ao; Fei Li (Environmental Research, 2026)

Ultrasound-targeted cavitation induced tumor vascular normalization and radiotherapy sensitization in breast cancer - Zichao Liu; Huai Yang; Zenan Zhang; Chenke Kuang; Liyong Deng; Yueyong Li; Linyuan Jin; Hongjun Nie; Guihua Wang; Meng Du; Zhiyi Chen (Science China Life Sciences, 2026)

Tidal current-induced local scour around offshore tripile foundations: A CFD study of flow-structure-sediment interaction - Hongjun Liu; Wei He; Qi Yang; Lu Jing; Peng Yu; Xinyu Liu; Jieru Zhao (Ocean Engineering, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Tire wear particles induce a functional trade-off in bioretention systems: Coupled effects on nitrogen removal and greenhouse gas emissions - Gaoju Zou; Niling Zou; Yinghui Tang; Qinyi Wang; Hongjun Xiao; Quanhong Chen; Zhen Liu; Kaifeng Wang; Fan Yang; Huachao Zhao; Yu Qin; Anke Du; et al. (Environmental Research, 2026)

A multi-scale assessment of topographic anisotropy on Land Surface Emissivity and Temperature retrieval over the Yarlung Tsangpo River basin - Hongjun Zhu; Xin Pan; Shanhu Jiang; Xingwang Fan; Kevin Tansey; Zhenwei Wang; Rufat Guluzade; Matthew Payne; Jie Yuan; Suyi Liu; Zi Yang; Yingbao Yang (International Journal of Remote Sensing, 2026)

Seed dispersal drives competition between pair-growing trees: implications for forest community dynamics - Xifu Yang; Haifeng Gu; Guangshun Jiang; Ke Rong; Hongjun Li; Qinghua Zhao; Yanhui Guan; Feifei Yang; Wentao Zhang; Tongzuo Zhang; Zhibin Zhang (Plant Ecology, 2026)

Health risks from PM2.5-bound heavy metals from religious burning activities on the plateau - Zhaoquan Yu; Lei Yang; Jiawei Yin; Haomiao Niu; Zhou Xu; Hao Qin; Liuyang Guo; Yan Liu; Lin Wu; Qijun Zhang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Efficient and tunable fabrication of hollow vaterite microspheres by micro-nano bubbles and mechanism study - Yuan Xin; Hongjun Yang; Huaiyou Wang (Journal of Environmental Chemical Engineering, 2026)

A fidelity-preserved organic geochemical study of the Cambrian and Ordovician black shales in the Tarim Basin, Northwest China - Huajian Wang; Jiaquan Zhou; Yunfeng Yang; Bo Yang; Shuang Gao; Hongjun Wu; Yingjie Yang; Chi Zhang; Yiran Lu; Wenyang Wang; Wang Zhang (International Journal of Coal Geology, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Enhancement of vortex-induced vibration energy harvesting using cactus-inspired bluff body attachments - Shiyong Yang; Hongjun Zhu; Junlei Wang (Ocean Engineering, 2026)

Quantitative assessment impact of anthropogenic heat flux on global urban evapotranspiration retrieval at multiple temporal scales - Zi Yang; Xin Pan; Hongjun Zhu; Fanggang Li; Xiangjin Meng; Rufat Guluzade; Yuanbo Liu; Suyi Liu; Wen He; Zhenwei Wang; Yingbao Yang (Journal of Hydrology, 2026)

Evaluating the effectiveness of tightened emission standards in reducing real-world vehicle emissions: Evidence from on-road testing and inventory analysis - Lei Yang; Zhaoquan Yu; Haomiao Niu; Hao Qin; Jiawei Yin; Zhou Xu; Yan Liu; Lin Wu; Jianfei Peng; Hongjun Mao; Qijun Zhang (Journal of Cleaner Production, 2026)

Improving GLASS AVHRR-derived terrestrial shortwave blue-sky albedo using GLASS MODIS-derived albedo: a global long-term study - Zi Yang; Hongjun Zhu; Jie Yuan; Rufat Guluzade; Xin Pan; Xu Ding; Suyi Liu; Congbao Zhu; Yuqian Li; Longlong Guo; Yingbao Yang (International Journal of Remote Sensing, 2026)

Flow-induced vibration energy harvesting performance enhanced with convergent-acceleration effect - Hongjun Sun; Zeyao Yang; Jinxia Li; Zhen Yang (Ocean Engineering, 2026)

Liquid fuel intrusion causes carbon canister deterioration and excess evaporative VOC emissions from in-use vehicles - Pengfei Song; Yan Liu; Qiang Chen; Jingyu Liu; Xueying Zeng; Tianlong Xing; Rui Zhang; Chongzhi Zhong; Taiyu Zhang; Ning Yang; Jianfei Peng; Hongjun Mao (Journal of Hazardous Materials, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

New insights into the characteristic flavor formation of Sichuan fermented sausages driven by liquid smoke addition: An integrated study based on microbiomics, flavoromics, and untargeted metabolomics - Dong Zhang; Xinrui Xie; Changlian Yu; Yuwei Liu; Li Yang; Chang Su; Xingzhong Zhang; Hongjun Li; Jie Tang (International Journal of Food Microbiology, 2026)

Novel anti-inflammatory peptides identified from beef tripe by network pharmacology, molecular docking, and in vitro study in RAW264.7 murine macrophages - Xuelian Sun; Zhifei He; Li Yang; Hongjun Li (Food Bioscience, 2026)

Spatiotemporal patterns of super-emitting diesel vehicles: A scalable remote sensing framework for urban emission hotspot mitigation - Junxia Gao; Yan Liu; Ning Yang; Zeping Cao; Jing Zhao; Lin Wu; Wentian Xu; Binfeng Yan; Zhengyu Jia; Hongjun Mao (Atmospheric Pollution Research, 2026)

System-Level Optimization of AUV Swarm Control and Perception: An Energy-Aware Federated Meta-Transfer Learning Framework with Digital Twin Validation - Zinan Nie; Hongjun Tian; Yijie Yin; Yuhan Zhou; Wei Li; Yang Xiong; Yichen Wang; Zitong Zhang; Yang Yang; Dongxiao Xie; Manlin Wang; Shijie Huang (Journal of Marine Science and Engineering, 2026)
Deep-sea exploration increasingly relies on Autonomous Underwater Vehicles (AUVs) to enable persistent, wide-area surveying in harsh and uncertain environments. In practice, however, deployments are constrained by tight energy budgets and bandwidth-limited, intermittent acoustic links, which complicate mission-level coordination. Moreover, many existing systems treat perception and control as loosely coupled modules, often resulting in redundant sensing, inefficient communication, and degraded overall performance—particularly under heterogeneous sensing modalities and shifting geological conditions. To address these challenges, we propose a hierarchical Federated Meta-Transfer Learning (FMTL) framework that tightly integrates collaborative perception with adaptive control for swarm optimization. The framework operates at three levels: (1) Representation Learning aligns heterogeneous sensors in a shared latent space via a physics-informed contrastive objective, substantially reducing communication overhead; (2) Meta-Learning Adaptation enables rapid transfer and convergence in new environments with minimal data exchange; and (3) Energy-Aware Control realizes closed-loop exploration by coupling Federated Explainable AI (FXAI) with decentralized multi-agent reinforcement learning (MARL) for path planning under energy constraints. Validated in high-fidelity hardware-in-the-loop simulations and a digital-twin environment, FMTL outperforms state-of-the-art baselines, achieving an AUC of 0.94 for target identification. Furthermore, an energy–intelligence Pareto analysis demonstrates a 4.5× improvement in information gain per Joule. Overall, this work provides a physically consistent and communication-efficient blueprint for the optimization and control of next-generation intelligent marine swarms.

Real-world key-process emission factors optimized environmental impact from passenger car tires’ PM2.5 and typical chemicals throughout lifecycle - Tiange Fang; Lei Sheng; Qiang Zeng; Guang Yang; Jinsheng Zhang; Wendi Wei; Jianfei Peng; Lin Wu; Ting Wang; Jing Zhang; Hongjun Mao (Journal of Hazardous Materials, 2026)

Counter-cation engineering in polyoxovanadate cathodes: Unlocking superior zinc-ion storage stability via NH4+ induced hydrogen bond networks - Tiantian Guan; Chunxi Ren; Kunxuan Li; Yu Zhang; Fan Yang; Lei Wang; Qing Han; Xuejing Qiu; Lingling Xie; Hongjun Chen; Xiaobo Ji; Jianmin Ma; et al. (Chemical Engineering Journal, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

Multiscale thermodynamic insights into membrane fouling control by biochar-activated peroxymonosulfate pretreatment: Synergy of oxidation and adsorption - Mingjing Xie; Wenfa Yang; Xiaoni Zhou; Biyan Wang; Jiaqi Liu; Xiao Xu; Liguo Shen; Hanmin Zhang; Meijia Zhang; Wei Yu; Jiaheng Teng; Hongjun Lin; et al. (Water Research, 2026)

Ammonia emission from real-world in-use vehicle fleets in a megacity in China - based on tunnel measurement - Jiliang Guo; Jinsheng Zhang; Ainan Song; Hui Tong; Jingchun Tang; Ning Yang; Zhuofei Du; Qijun Zhang; Ting Wang; Lin Wu; Jianfei Peng; Hongjun Mao (Journal of Environmental Sciences, 2026)

Organic electron donor limitation triggers metabolic trade-offs in anaerobic granular sludge: The pivotal role of Fe-mediated electron bifurcation - Bochuang Huang; Yangyang Li; Jinhao Zhu; Juncong Zou; Dexin Wang; Chunping Yang; Hongjun Han; Wencheng Ma (Chemical Engineering Journal, 2026)

Proline-functionalized zein nano delivery system enables sustained brassinolide release for enhanced salt stress tolerance in cucumber cultivation - Jihao Zuo; Ruopeng Lan; Jinting Cai; Long Chen; Dongyan Yang; Huayao Chen; Li Hao; Ximing Zhong; Xinhua Zhou; Hongjun Zhou (Chemical Engineering Journal, 2026)

Lacticaseibacillus paracasei subsp. paracasei Q- 1 Exhibits Good Safety and Effectively Prevents Escherichia coli K99-Induced Diarrhea in Mice - Fengjie Wang; Li Chen; Yang Li; Guangping Gao; Yanan Wang; Ruili Shi; Hongjun Zhang; Yingyu Chen; Rui Cao; Qiumei Shi; Tonglei Wu (Probiotics and Antimicrobial Proteins, 2026)

Evolving Collective Intelligence for Unmanned Marine Vehicle Swarms: A Federated Meta-Learning Framework for Cross-Fleet Planning and Control - Yuhan Ye; Hongjun Tian; Yijie Yin; Yuhan Zhou; Yang Xiong; Zi Wang; Yaojiang Liu; Zinan Nie; Zitong Zhang; Yichen Wang; Jingyu Sun (Journal of Marine Science and Engineering, 2025)
The development of robust autonomous maritime systems is fundamentally constrained by the “data silo” problem, where valuable operational data from disparate fleets remain isolated due to privacy concerns, severely limiting the scalability of general-purpose navigation intelligence. To address this barrier, we propose a novel Federated Meta-Transfer Learning (FMTL) framework that enables collaborative evolution of unmanned surface vehicle (USV) swarms while preserving data privacy. Our hierarchical approach orchestrates three synergistic stages: (1) transfer learning pre-trains a universal “Sea-Sense” foundation model on large-scale maritime data to establish fundamental navigation priors; (2) federated learning enables decentralized fleets to collaboratively refine this model through encrypted gradient aggregation, forming a distributed cognitive network; (3) meta-learning allows for rapid personalization to individual vessel dynamics with minimal adaptation trials. Comprehensive simulations across heterogeneous fleet distributions demonstrate that our federated model achieves a 95.4% average success rate across diverse maritime scenarios, significantly outperforming isolated specialist models (63.9–73.1%), while enabling zero-shot performance of 78.5% and few-shot adaptation within 8–12 episodes on unseen tasks. This work establishes a scalable, privacy-preserving paradigm for collective maritime intelligence through swarm-based learning.

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Assessing the spatial-temporal wave energy characteristics along the southeastern coast of China in a wave simulation study - Jie Yang; Chen Wang; Hongjun Zhao (Ocean Engineering, 2025)

Enhanced built-in electric field and strong interfacial electronic coupling in 2D/2D BiO2-x/Ti3C2 Schottky heterojunction boost exciton dissociation for sustainable molecular oxygen activation toward 100 % singlet oxygen generation - Chongyang Yang; Song Tian; Yanyan Liu; Liguo Shen; Cheng Chen; Yanchao Xu; Leihong Zhao; Bisheng Li; Mingzhu Zhou; Hongjun Lin (Journal of Environmental Chemical Engineering, 2025)

Transition metal phosphides: Electron buffer agents for selective and durable seawater oxidation - Jing Zhang; Yang Yang; Kaixuan Huo; Zhiqiang Qiao; Zunjian Ke; Nana Li; Dandan Yuan; Jing Gu; Hongjun Wu; Zhida Li (Chemical Engineering Journal, 2025)

Evaluation of feeding intensity in pearl gentian grouper under factory aquaculture environment based on multi-feature fusion and MDGSNet model - Zeshuang Ma; Hongpo Wang; Hong Zhou; Yunchen Tian; Jianing Quan; Haohui Liu; Zhanshuo Sun; Hongjun Yang (Aquaculture International, 2025)

Decreased myocardial glucose uptake precedes cardiac dysfunction in hindlimb unloading mice revealed by dynamic 18F-FDG PET imaging - Min Yang; Yifan Qiu; Lei Bi; Jianzhong Xian; Zhijun Li; Jijin Yao; Hongjun Jin (Life Sciences in Space Research, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Widely targeted metabolomics and GC–IMS reveal flavor and metabolite variations in Rex and Hyla rabbit meat under different cooking methods - Shuyun Liu; Hongjun Li; Bin Wen; Li Yang; Xuelian Sun; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

A source-oriented precise risk assessment of trace metal(loid)s in sediments of the Yangtze River Basin - Kuo Pang; Lu Liu; Junlan Yang; Hongjun Zhao; Wei Hu; Xiaonan Ji; Yali Guo; Min Li (Environmental Pollution, 2025)

Magnetic-field-assisted fabrication of Fe3O4-enhanced thin-film nanocomposite polyamide nanofiltration membranes with enhanced separation performance - Congcong Zhou; Zhihao Chen; Jingfen Yuan; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2025)

Magnetically directed interfacial polyamerization of Fe3O4@CdS@CQDs-embedded polyamide nanofiltration membranes with enhanced separation and photocatalytic self-cleaning performance - Erqiao Chen; Zhihao Chen; Zhongting Liu; Mingzhu Zhou; Bisheng Li; Renjie Li; Liguo Shen; Yang Jiao; Hongjun Lin; Yanchao Xu (Chemical Engineering Journal, 2025)

Molecular design of polyoxovanadate cathodes for advanced AZIBs: Multielectron redox chemistry and structural engineering - Yu Zhang; Tiantian Guan; Fan Yang; Qing Han; Lingling Xie; Xuejing Qiu; Lei Wang; Hongjun Chen; Yuling Wang; Xiaobo Ji; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2025)

Revealing higher-order topological bulk-boundary correspondence in bismuth crystal with spin-helical hinge state loop and proximity superconductivity - Dongming Zhao; Yang Zhong; Tian Yuan; Haitao Wang; Tianxing Jiang; Yang Qi; Hongjun Xiang; Xingao Gong; Donglai Feng; Tong Zhang (Science Bulletin, 2025)

Novel CoMo-LDH integration enhanced permeability and self-cleaning of MXene-based membrane for efficient water treatment - Qianqian Zeng; Zhiyu Zhao; Yue Wang; Siyuan Chen; Hua Li; Cheng Chen; Wei Yu; Jiaheng Teng; Hongjun Lin; Yu Yang; Liguo Shen (Chemical Engineering Journal, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Competitive effects and environmental factors driving heavy metal leaching in stabilized municipal solid waste incineration fly ash under extreme conditions - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Chuanfu Wu; Shu Liu (Journal of Hazardous Materials, 2025)

Mimicking butterflies: Thermal adaptive management material with shape memory Janus arrays - Guangyao Hou; Xinzhi Wang; Henghao Liu; Hongjun Kang; Xin Jia; Yang Li; Wei Qin; Xiaohong Wu (Chemical Engineering Journal, 2025)

Spatiotemporal Meta-Reinforcement Learning for Multi-USV Adversarial Games Using a Hybrid GAT-Transformer - Yang Xiong; Shangwen Wang; Hongjun Tian; Guijie Liu; Zihao Shan; Yijie Yin; Jun Tao; Haonan Ye; Ying Tang (Journal of Marine Science and Engineering, 2025)
Coordinating Multi-Unmanned Surface Vehicle (USV) swarms in complex, adversarial maritime environments is a significant challenge, as existing multi-agent reinforcement learning (MARL) methods often fail to capture intricate spatiotemporal dependencies, leading to suboptimal policies. To address this, we propose Adv-TransAC, a novel Spatio-Temporal Meta-Reinforcement Learning framework. Its core innovation is a hybrid GAT-transformer architecture that decouples spatial and temporal reasoning: a Graph Attention Network (GAT) models instantaneous tactical formations, while a transformer analyzes their temporal evolution to infer intent. This is combined with an adversarial meta-learning mechanism to enable rapid adaptation to opponent tactics. In high-fidelity escort and defense simulations, Adv-TransAC significantly outperforms state-of-the-art MARL baselines in task success rate and policy robustness. The learned policies demonstrate the emergence of complex cooperative behaviors, such as intelligent risk-aware coordination and proactive interception maneuvers. The framework’s practicality is further validated by a communication-efficient federated optimization architecture. By effectively modeling spatiotemporal dynamics and enabling rapid adaptation, Adv-TransAC provides a powerful solution that moves beyond reactive decision-making, establishing a strong foundation for next-generation, intelligent maritime platforms.

Heat stroke-induced central nervous system injury: Mechanisms and therapeutic perspectives - Wenjun Yang; Zhen Gao; Chengjin Wang; Min Wang; Yuan Cao; Yun Li; Shaoqing Shi; Yiqi Wu; Lu Wang; Hongjun Kang (Journal of Thermal Biology, 2025)

Pioneering integration of bimetallic Fe2O3-Mn2O3 nanoparticles into polyamide nanofiltration membranes for enhanced antibiotic wastewater treatment - Yidan Ding; Hanchen Zhang; Liguo Shen; Yang Jiao; Yanchao Xu; Hongjun Lin (Journal of Cleaner Production, 2025)

Rhubarb with Different Cooking Methods Restored the Gut Microbiota Dysbiosis and SCFAs in Ischemic Stroke Mice - Jing Xu; Taotao Liu; Fuzhu Pan; Xuan Ao; Lan Wang; Rixin Liang; Yuxin Lei; Yurong Ding; Miao Yu; Li Li; Hongjun Yang (Molecular Neurobiology, 2025)

Data-Driven Multi-Scale Channel-Aligned Transformer for Low-Carbon Autonomous Vessel Operations: Enhancing CO2 Emission Prediction and Green Autonomous Shipping Efficiency - Jiahao Ni; Hongjun Tian; Kaijie Zhang; Yihong Xue; Yang Xiong (Journal of Marine Science and Engineering, 2025)
The accurate prediction of autonomous vessel CO2 emissions is critical for achieving IMO 2050 carbon neutrality and optimizing low-carbon maritime operations. Traditional models face limitations in real-time multi-source data analysis and dynamic cross-variable dependency modeling, hindering data-driven decision-making for sustainable autonomous shipping. This study proposes a Multi-scale Channel-aligned Transformer (MCAT) model, integrated with a 5G–satellite–IoT communication architecture, to address these challenges. The MCAT model employs multi-scale token reconstruction and a dual-level attention mechanism, effectively capturing spatiotemporal dependencies in heterogeneous data streams (AIS, sensors, weather) while suppressing high-frequency noise. To enable seamless data collaboration, a hybrid transmission framework combining satellite (Inmarsat/Iridium), 5G URLLC slicing, and industrial Ethernet is designed, achieving ultra-low latency (10 ms) and nanosecond-level synchronization via IEEE 1588v2. Validated on a 22-dimensional real autonomous vessel dataset, MCAT reduces prediction errors by 12.5% MAE and 24% MSE compared to state-of-the-art methods, demonstrating superior robustness under noisy scenarios. Furthermore, the proposed architecture supports smart autonomous shipping solutions by providing demonstrably interpretable emission insights through its dual-level attention mechanism (visualized via attention maps) for route optimization, fuel efficiency enhancement, and compliance with CII regulations. This research bridges AI-driven predictive analytics with green autonomous shipping technologies, offering a scalable framework for digitalized and sustainable maritime operations.

Chelation treatment for heavy metals in municipal solid waste incineration fly ash: 300-Day study on stability and environmental risk - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Xiaona Wang; Ming Gao; Qunhui Wang; Chuanfu Wu (Waste Management, 2025)

On the capability of SWAN model for South Atlantic Ocean wave simulation - Hongjun Zhao; Peixian Chen; Wanwei Zhang; Shichang Yan; Jie Yang; Jun Kong (Ocean Dynamics, 2025)

Diversity and Function of Strawberry Endophytic Bacterial Communities Associated with Host Genotype and Niche - Hongjun Yang; Xu Zhang; Zhiming Yan; Yuanhua Wang; Quanzhi Wang; Bei Lu; Jiajia Chen; Xiao Wu (Current Microbiology, 2025)

Integrally moldable carbon fiber evaporator using a weaving process for efficient and stable solar water desalination - Jinyong Yao; Minyuan Feng; Naidan Zhang; Yongheng Zhou; Haroon A.M. Saeed; Weilin Xu; Jianquan Li; Hongjun Yang (Desalination, 2025)

FePS3-Nanosheets-Integrated multifunctional nanocomposite hydrogel for multimodal synergistic osteosarcoma therapy and enhanced bone regeneration - Bing Ye; Xirui Jing; Yanlin Su; Wenzhe Sun; Qing Gao; Lian Zeng; Hongwei Lu; Shuo Tang; Yizhou Wan; Tingfang Sun; Zekang Xiong; Xiao Lv; et al. (Chemical Engineering Journal, 2025)

Unveiling environmental adaptability of magnetite-mediated Feammox system: Multiple pathways identification, metabolic responses and engineering potential analysis - Xiangzhuang Fu; Yangyang Li; Weiwei Huang; Dexin Wang; Chunping Yang; Hongjun Han (Chemical Engineering Journal, 2025)

Fluxapyroxad induces chronic colonic inflammation via inhibiting intestinal aryl hydrocarbon receptors in mice - Yue Cao; Shouchun Xiao; Yaofeng Fang; Jiaxing Yang; Zeyu Hu; Hongjun Zhang; Xueke Liu; Donghui Liu; Zhiqiang Zhou; Peng Wang (Science of The Total Environment, 2025)

Advanced three-dimensional numerical simulation on influence of MS2AF on scour protection considering seabed response: A coupled CFD-FEM method - Chenghao Zhu; Xinyu Liu; Qi Yang; Wenkun Zang; Hongjun Liu; Xiaolong Liu (Ocean Engineering, 2025)

Effect of cooking treatment on protein digestibility, peptide profile and potential bioactive peptides of beef tripe during in vitro gastrointestinal digestion - Xuelian Sun; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2025)

Green β-cyclodextrin interlayered crumpled polyamide membranes for effective desalination - Jian Yu; Ling Zhang; Hongguang Sun; Renjie Li; Die Ling Zhao; Liguo Shen; Hongjun Lin; Yang Jiao; Yanchao Xu (Desalination, 2025)

Multifactorial Controls on the Dongdaobei Submarine Canyon System, Xisha Sea, South China Sea - Meijing Sun; Hongjun Chen; Chupeng Yang; Xiaosan Hu; Jie Liu (Journal of Marine Science and Engineering, 2025)
The submarine canyons system is the most widely distributed geomorphic unit on the global continental margin. It is an important concept in the field of deep-water sedimentation and geohazards. Based on high-resolution multibeam bathymetry and two-dimensional seismic data, the dendritic canyon system north of Dongdao island is studied at the eastern Xisha area of the South China Sea. The Dongdaobei submarine canyon is distributed in water depths between 1000 and 3150 m. The main source area in the upper course of the canyon originates from the northwest of Dongdao platform and the Yongxing platform. The sediments from the source area are transported to the main canyon in the form of various gravity flows. Landslides on the slope significantly impact canyon evolution by delivering sediment to the canyon head and causing channel deflection through substrate failure and flow-path reorganization. A large number of pockmarks are distributed around the north slope of the main canyon. The small-scale channels, which are formed as a result of the continuous erosion of the pockmark chains, are connected to the canyon sidewalls. The seamounts are distributed along the south bank of the canyon, exerting a controlling influence on the directional changes in the main canyon’s downstream segment. The formation and evolution of the Dongdaobei submarine canyon are primarily influenced by several factors, including tectonic activity and inherited negative topography, erosion by sedimentary gravity flows, sediment instability, and the shielding effect of seamounts.

The relationship between high-quality development and ecosystem health in China's urban agglomerations - Bin Yang; Xiaohan Ma; Jirong Li; Haochen Yu; Hongjun Sui; Fu Chen; Li Tan (Journal of Environmental Management, 2025)

A novel method to improve the anti-ageing ability of bitumen by organic LDHs/SBS composite: Preparation, performance evaluation and mechanism analysis - Canlin Zhang; Shuai Yang; Ting Wang; Song Xu; Peng Jin; Hongjun Dong; Yi Zhang; Yu Chen (Fuel, 2025)

Long-term diversified cropping promotes wheat yield and sustainability across contrasting climates: Evidence from China and Switzerland - Zhengjun Yan; Yi Xu; Juncong Chu; Thomas Guillaume; Luca Bragazza; Hongjun Li; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Impact of flow velocity on growth performance, muscle texture, and nutritional composition in seabass (Lateolabrax maculatus) - Fan Fei; Yingying Fang; Zhiwen Zhu; Xinyu Liu; Ao Li; Jiawen Zhang; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Wensheng Li; Chuanxin Zhang; Baoliang Liu (Aquaculture International, 2025)

Astral-based DIA proteomics explored the flavor enhancement mechanism of Chinese traditional smoked bacon by staphylococcal co-fermentation - Li Yang; Hongjun Li; Han Wu; Xueling Sun; Shuyun Liu; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

The heterointerface engineering triggers hydrogen spillover through synergistic effect in alkaline media - Qiang Zhang; Yuhong Bian; Sunpeng Shan; Zhiwei Shu; Nana Wang; Xiao Zhang; Yanchao Xu; Hongjun Lin; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2025)

Identification of multiple miRNA-encoded peptide reveals OsmiPEP162a putatively stabilizes OsMIR162 in rice - Jianping Zhou; Rui Zhang; Qinqin Han; Hongjun Yang; Wei Wang; Yibo Wang; Xuelian Zheng; Fan Luo; Guangze Cai; Yong Zhang (Plant Cell Reports, 2025)

Highly responsive cryogel based sensing platform by encapsulating programmed DNA for colorimetric detection of 17β-estradiol - Yujia Guo; Jiaxuan Xiao; Fengxiang Ai; Xiaofeng Yang; Kun Zeng; Yuhan Wang; Xuesong Li; Zhen Zhang; Hongjun Zhao (Analytica Chimica Acta, 2025)

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Membrane fouling mechanisms in the presence of microplastics and organic matter: The unexpected mitigating role of Ca2+ - Xiaoni Zhou; Wenfa Yang; Hongjun Lin; Biyan Wang; Mingjing Xie; Hao Fang; Hanmin Zhang; Meijia Zhang; Jiaheng Teng (Science of The Total Environment, 2024)

A novel application of industrial waste bischofite for the anti-aging property of asphalt: Synthesis of organic layered double hydroxide and performance evaluation - Hongjun Dong; Canlin Zhang; Yiwei Weng; Ting Wang; Song Xu; Shijie Ma; Shuai Yang; Yu Chen (Journal of Cleaner Production, 2024)

Super-hydrophilic membranes fabricated by synergistic integration of covalent organic framework nanoflowers and hydrophilic layers for efficient oil-water separation - Baoliang Dai; Yidan Ding; Cheng Chen; Liguo Shen; Die Ling Zhao; Yang Jiao; Hongjun Lin; Yanchao Xu (Desalination, 2024)

Nonlinear seismic response analysis of liquefiable sites based on effective stress method - Hongjun He; Hanwen Ji; Yang Shi; Xiaohua Ke; Yu Miao (Computers and Geotechnics, 2024)

Effects of biochar produced from distiller grains on agronomic performances of sorghum (Sorghum bicolor L.) and greenhouse gas emissions from soil - Hongjun YANG; Suyi ZHANG; Jingyu HU; Jianguo HUANG; Zonghua AO; Xiaoqin WANG; Zhe LI; Xuepin LIAO (Pedosphere, 2024)

Which biofilm reactor is suitable for degradation of 2,4-dimethylphenol, focusing on bacteria, algae, or a combination of bacteria-algae? - Jingxin Shi; Ning Wan; Shuhui Yang; Yuanyuan Yang; Hongjun Han (Journal of Hazardous Materials, 2024)

Unraveling the mechanism of aroma loss during prolonged hot air drying of non-smoked bacon: Insights into aroma compounds generation and retention - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Research International, 2024)

Unraveling the influence of lipids on aroma generation in non-smoked bacon during boiling through untargeted lipidomics analysis - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Bioscience, 2024)

Visualizing of engineered five-helix bundle protein for blocking SARS-CoV-2 variants in live animals - Jianzhong Xian; Zhijun Li; Hongbin Huang; Lei Bi; Zhifeng Guan; Guolong Huang; Min Yang; Zhizeng Gao; Jijin Yao; Zhongzhen Su; Hongjun Jin (Chemical Engineering Journal, 2024)

Quasi-FeCo-MOF/CoS amorphous Nanosheets: A stable and highly active catalyst for electrocatalytic water splitting and monosaccharide oxidation - Yanqiu Xu; Qiang Zhang; Nana Wang; Lijun Huang; Xiao Zhang; Hongjun Lin; Yanchao Xu; Jianrong Chen; Yang Jiao (Chemical Engineering Journal, 2024)

Transcriptomics and Metabolomics Unveil the Neuroprotection Mechanism of AnGong NiuHuang (AGNH) Pill Against Ischaemic Stroke Injury - Liangliang Tian; Guangzhao Cao; Xiaotong Zhu; Lihan Wang; Jingyi Hou; Yi Zhang; He Xu; Lixia Wang; Shicong Wang; Chen Zhao; Hongjun Yang; Jingjing Zhang (Molecular Neurobiology, 2024)

Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

Biomimetic tree structure for efficient solar steam generation and water purification - Haroon A.M. Saeed; Veronica Valerian Kazimoto; Hongjun Yang (Journal of Water Process Engineering, 2024)

Exhaust and evaporative volatile organic compounds emissions from vehicles fueled with ethanol-blended-gasoline - Ruikang Li; Chongzhi Zhong; Yang Ning; Yan Liu; Pengfei Song; Ruiguang Xu; Hongjun Mao (Environmental Pollution, 2024)

Review of utilization of bamboo fiber in asphalt modification: Insights into preparation, performance, reinforcement, and challenges - Haibin Li; Songjiang Liu; Fan Yang; Siyu He; Hongjun Jing; Xiaolong Zou; Zhigang Li; Yanping Sheng (Journal of Cleaner Production, 2024)

New insights into the dominance of mixed fermentation of Staphylococcus cohnii and Staphylococcus saprophyticus in Chinese bacon: Complete genomic and comparative genomic perspectives - Li Yang; Hongjun Li; Han Wu; Xuelian Sun; Shuyun Liu; Dong Zhang; Chang Su; Zhifei He (Food Research International, 2024)

Quantitative proteomic analysis to identify potential biomarkers linked to quality traits of beef tripe from different sources - Xuelian Sun; Zhifei He; Li Yang; Han Wu; Hongjun Li (Food Chemistry, 2024)

Effect of heme proteins on the lipid molecule profile and aroma formation during hot air drying of non-smoked bacon - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2024)

Mn-O bond Engineering Mitigating Jahn-Teller Effects of Manganese Oxide for Aqueous Zinc-ion Battery Applications - Meng Xie; Xiao Zhang; Ran Wang; Yang Jiao; Zhiwei Shu; Sunpeng Shan; Yuhong Bian; Hongjun Lin; Jianrong Chen; Yanchao Xu (Chemical Engineering Journal, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

A contagious disease caused serious damage to Gracilariopsis lemaneiformis cultivation in China - Tong Pang; Feng Wang; Xiaobin Yang; Jianguo Liu; Hongjun Xu; Qunqun Guo; Liyuan Liu (Journal of Applied Phycology, 2024)

Exploring potential lipid precursors for aroma formation in non-smoked bacon during hot air drying via untargeted lipidomics and oxidation model - Han Wu; Zhifei He; Li Yang; Hongjun Li (Meat Science, 2024)

Effect of staphylococci fermentation and their synergistic Lactobacillus on the physicochemical characteristics and nonvolatile metabolites of Chinese bacon - Li Yang; Hongjun Li; Han Wu; Shuyun Liu; Zhifei He (Meat Science, 2024)

Toxic effect and mechanism of β-cypermethrin and its chiral isomers on HTR-8/SVneo cells - Chaojin Si; Hongjun Yang; Xiaoyan Wang; Qiaoxin Wang; Min Feng; Huayue Li; Yuqi Feng; Jiayuan Zhao; Ying Liao (Pesticide Biochemistry and Physiology, 2024)

Selenium in plants: A nexus of growth, antioxidants, and phytohormones - Sufian Ikram; Yang Li; Chai Lin; Debao Yi; Wang Heng; Qiang Li; Lu Tao; Yu Hongjun; Jiang Weijie (Journal of Plant Physiology, 2024)

Effect of Naoxintong Capsule on Microglia and Proteomics of Cortex After Myocardial Infarction in Rats - Mengli Chang; Yuxin Lei; Jing Zhang; Jing Xu; Hongwei Wu; Shihuan Tang; Hongjun Yang (Molecular Neurobiology, 2024)

Enhancing mechanism of extrusion pretreatment on bioconversion of distiller’s grains into microbial protein feed - Chenjie Wang; Yao Liu; Ruoyun Yuan; Ling Xu; Chunhui Xin; Yang Tang; Chengye Ma; Shanfeng Chen; Hongjun Li (Animal Feed Science and Technology, 2024)

Simultaneously promoting CO2 permeability and selectivity of polyethylene oxide membranes via introducing CO2-philic KAUST-7 - Wen Hou; Jun Cheng; Yingyu Tan; Chen Yang; Xufeng Ren; Jinming Xie; Bangjiao Ye; Hongjun Zhang; Junhu Zhou (Fuel, 2024)

Highly efficient and selective electrosynthesis of urea via co-reduction of carbon dioxide and nitrate over the TiN catalyst - Hongjun Fang; Ze Wang; Chen-Han Kuo; Hongsheng Yang; Xinzhen Feng; Weijie Ji; Chak-Tong Au (Chemical Engineering Journal, 2024)

Taxonomic and functional dynamics of nirS denitrifiers along a salinity gradient in the Pearl River Estuary - Hongwei Zhou; Hao Zhang; Xinping He; Cheng Liu; Fozia; Qian Cui; Hongjun Yang; Chunyu Zhao; Han Zhang; Huanhuan Hu; Zongxiao Zhang (Frontiers in Marine Science, 2024)
Understanding the factors that shape the diversity, distribution, and function of denitrifying microbes is vital for managing nitrogen cycling in these ecosystems. This study explores the diversity, biogeographic distribution, assembly processes, interaction, and denitrification potential of the nirS -encoding microbial community ( nirS denitrifier) in the Pearl River Estuary based on high-throughput and metagenomics sequencing dataset. The results of this study show that salinity is a crucial regulatory environmental factor that determines the spatial distribution, phylogenetic turnover, and co-occurrence patterns of nirS denitrifiers. Additionally, the dissolved organic carbon (DOC), suspended sediment concentration (SSC), and dissolved oxygen (DO) in water also significantly impact the biodiversity and abundance of nirS denitrifiers. Furthermore, our findings demonstrate that, in comparison to environmental factors, the ecological and evolutionary characteristics of nirS denitrifiers play a more prominent role in regulating their denitrification potential, suggesting that alterations in the microbial community within dynamic changes in estuarine water can profoundly affect its denitrification function. Our results indicate the significant roles of denitrification microbial structure and phylogenetic characteristics in maintaining their ecological functions. Future studies should continue to explore the interactions between microbial communities and environmental factors to further elucidate the denitrification process in estuaries and its implications for ecosystem health and water quality.

Stabilization of heavy metals in municipal solid waste incineration fly ash using organic chelating agents: Insight into risk assessment and function mechanism - Ze Zhang; Yang Yu; Yi Rao; Ying Wang; Chunjiang Yu; Zhongli Luo; Hongjun Zhao; Amirhomayoun Saffarzadeh; Xiaona Wang; Chuanfu Wu; Qunhui Wang (Science of The Total Environment, 2024)

New insights into survival strategies and PCB bioremediation potential of resuscitated strain Achromobacter sp. HR2 under combined stress conditions - Jie Shi; Yingying Yang; Shusheng Zhang; Qihua Lin; Faqian Sun; Hongjun Lin; Chaofeng Shen; Xiaomei Su (Journal of Hazardous Materials, 2024)

Generation of key aroma compounds in fat and lean portions of non-smoked bacon induced via lipid pyrolysis reaction - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2024)

Unveiling the PCB biodegradation potential and stress survival strategies of resuscitated strain Pseudomonas sp. HR1 - Yingying Yang; Qian Zhang; Qihua Lin; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Environmental Pollution, 2024)

Staphylococcus inoculation enhances the sensorial attributes of Chinese bacon by coordinating the composition of flavor compounds through amino acid metabolism - Li Yang; Hongjun Li; Han Wu; Shunyun Liu; Zhifei He (Food Research International, 2024)

Assembly mechanisms of microbial communities in plastisphere related to species taxonomic types and habitat niches - Yi Sun; Hongjun Li; Jinyong Zhang; Haining Wang; Xiaoyu Cui; Xin Gao; Wenwen Qiao; Yuyi Yang (Marine Pollution Bulletin, 2024)

Innovative construction of nano-wrinkled polyamide membranes using covalent organic framework nanoflowers for efficient desalination and antibiotic removal - Baoliang Dai; Yijing Hu; Yidan Ding; Liguo Shen; Renjie Li; Dieling Zhao; Yang Jiao; Yanchao Xu; Hongjun Lin (Desalination, 2024)

Dynamical graph neural network with attention mechanism for epilepsy detection using single channel EEG - Yang Li; Yang Yang; Qinghe Zheng; Yunxia Liu; Hongjun Wang; Shangling Song; Penghui Zhao (Medical & Biological Engineering & Computing, 2024)

Effects of triclosan exposure on stem cells from human exfoliated deciduous teeth (SHED) fate - Shiwen Deng; Caifeng Li; Junqi Chen; Zhao Cui; Tong Lei; Hongjun Yang; Peng Chen (Science of The Total Environment, 2023)

Protective and immunomodulatory effects of mesenchymal stem cells on multiorgan injury in male rats with heatstroke - Yuyan Liu; Yun Li; Zihui Deng; Yan Zhao; Rui Yuan; Mengmeng Yang; Lu Wang; Yuan Fang; Dengfeng Ding; Feihu Zhou; Hongjun Kang (Journal of Thermal Biology, 2023)

Dynamic characteristics of net anthropogenic phosphorus input to the upper Yangtze River Basin from 1989 to 2019: Focus on the phosphate ore rich area in China - Junlan Yang; Min Li; Lu Liu; Hongjun Zhao; Wenqing Luo; Yali Guo; Xiaonan Ji; Wei Hu (Journal of Environmental Management, 2023)

Fabrication of a novel acid-resistant nanofiltration membrane with dual-charged functional layer for metal ions recovery - Lu Bai; Zhilu Li; Zhengjun Peng; Youjing Zhao; Hongjun Yang; Min Wang (Journal of Environmental Chemical Engineering, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Amplification-free microRNA profiling with femtomolar sensitivity on a plasmonic enhanced fluorescence nano-chip - Ruibin Hu; Yiyi Liu; Guanghui Wang; Jiahui Lv; Jingkai Yang; Hongjun Xiao; Ying Liu; Bo Zhang (Analytica Chimica Acta, 2023)

Health benefits of traffic-related PM2.5 and CO reduction—a case study of Tianjin, China, from 2015 to 2019 - Yunqian Chen; Zheng Ran; Ya-nan Wang; Xiaoping Liu; Pu Yang; Kun Han; Xiaoge Yin; Chao Zou; Rui Wu; Hongjun Mao; Taosheng Jin (Air Quality, Atmosphere & Health, 2023)

Assessing the performance of SWAN model for wave simulations in the Bay of Bengal - Wanwei Zhang; Hongjun Zhao; Guoping Chen; Jie Yang (Ocean Engineering, 2023)

Green light optimized speed advisory achieves fuel savings and CO2 emission reduction by profoundly impacting driving behavior - Xiaoyang Zhao; Zhenyu Jia; Ning Wei; Dongping Guo; Lu Yao; Jiawei Yin; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Dissolved organic matter evolution and straw decomposition rate characterization under different water and fertilizer conditions based on three-dimensional fluorescence spectrum and deep learning - Guang Yang; Hongwei Pan; Hongjun Lei; Wenbin Tong; Lili Shi; Huiru Chen (Journal of Environmental Management, 2023)

In-situ characterization of the size distribution of lubricant droplets in rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Nano-wrinkled polyamide membrane preparation via heterogeneous surface-regulated interfacial polymerization for enhanced desalination performance - Zhiwen Li; Yanchao Xu; Liguo Shen; Renjie Li; Yang Jiao; Hongjun Lin; Chuyang Y. Tang (Desalination, 2023)

Innovative role of polyvinylpyrrolidone in tailoring polyamide layer for high-performance nanofiltration membranes - Zhiwen Li; Shuilian Peng; Wentian Zhang; Jianzhen Zhang; Yang Jiao; Renjie Li; Liguo Shen; Hongjun Lin; Yanchao Xu (Desalination, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

Genetic sequencing provides insights into molecular and genetic mechanisms of Lysobacter enzymogenes HYP18 involved in soil organic nitrogen and phosphorus mobilization and plant growth promotion - Liyuan Peng; Jianguo Huang; Chunyang Huang; Hongjun Yang (Plant and Soil, 2023)

Targeted Energy Metabolomics Combined with Spatial Metabolomics Study on the Efficacy of Guhong Injection Against Cerebral Ischemia Reperfusion - Huanhuan Wang; Zhenkun Li; Guangzhao Cao; Liying Tang; Rui Zhou; Caifeng Li; Jingjing Zhang; Hongwei Wu; Xianyu Li; Hongjun Yang (Molecular Neurobiology, 2023)

Compound hot extremes exacerbate forest growth decline in dry areas but not in humid areas in the Northern Hemisphere - Hongjun Yang; Wenjing Tao; Qimei Ma; Hanfeng Xu; Lingfeng Chen; Hongjun Dong; Yuchuan Yang; Nicholas G. Smith; Lei Chen (Agricultural and Forest Meteorology, 2023)

Seasonal implications for taxonomic sufficiency to simplify M-AMBI methodology in the coastal area adjacent to a eutrophic estuary - Chenman Yang; Hongjun Song; Yi Sun; Pengfei Xie; Yuan Liu; Hongjun Li (Acta Oceanologica Sinica, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Characteristics, sources, and health risks of inorganic elements in PM2.5 and PM10 at Tianjin Binhai international airport - Qijun Zhang; Lei Yang; Jianfei Peng; Lin Wu; Hongjun Mao (Environmental Pollution, 2023)

Breaking the cost barrier: polydopamine@NixCo100-x nanotubes as efficient photocatalysts for organic pollutant degradation - Qianqian Zeng; Hongjun Lin; Yang Qu; Zhengyi Huang; Ning Kong; Lei Han; Cheng Chen; Bisheng Li; Jiaheng Teng; Yanchao Xu; Liguo Shen (Journal of Cleaner Production, 2023)

Energy saving and emission reduction effects from the application of green light optimized speed advisory on plug-in hybrid vehicle - Zhenyu Jia; Ning Wei; Jiawei Yin; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Flexible dual-functionalized hyaluronic acid hydrogel adhesives formed in situ for rapid hemostasis - Penghui Fan; Qi Dong; Junfeng Yang; Yun Chen; Hongjun Yang; Shaojin Gu; Weilin Xu; Yingshan Zhou (Carbohydrate Polymers, 2023)

Softening/Hardening Damage Model and Numerical Implementation of Seabed Silt-Steel Interface in Yellow River Underwater Delta - Peng Yu; Honghua Liu; Lin Geng; Shuai Wang; Yang Yu; Chenghao Zhu; Qi Yang; Hongjun Liu; Yong Guan (Journal of Marine Science and Engineering, 2023)
The interaction between soil and structure is a research hotspot in ocean engineering, and the shear performance of interfaces is an essential factor affecting the bearing capacity of offshore structures. Taking the Yellow River Underwater Delta as the research area, the Softening/Hardening damage model of the silt–steel interface and the determination method of model parameters are proposed based on the statistical damage theory. Through the interface monotonic shear test under the conditions of different normal stress, roughness and water content, the shear mechanical properties and volumetric deformation laws on the silt–steel interface are analyzed, and the damage model parameters are obtained. Finally, a FRIC subroutine for the damage model was developed based on ABAQUS. The research results indicate the following: (1) The interface between silt and steel exhibits two characteristics, softening/hardening and shear shrinkage/expansion, under different conditions. Roughness significantly impacts interfacial cohesion, while water content mainly affects the internal friction angle. (2) The softening model based on the classic rock damage model can better simulate the stress–strain relationship of the silt–steel interface under high normal stress and low water content. In contrast, the hardening model based on the classic hyperbola model can better simulate the stress–strain relationship under low normal stress and high water content. The calculated results of the softening/hardening model agree with the experimental results, and the model has 7 parameters. (3) The developed FRIC subroutine can effectively simulate the nonlinear mechanical behavior of the interface between silt and steel. The research results provide a reference for exploring the stability analysis of offshore structures considering interface weakening effects.

Experimental study of the lubricant-refrigerant flow in a rotary compressor - Puyuan Wu; Jun Chen; Paul E. Sojka; Yang Li; Hongjun Cao (International Journal of Refrigeration, 2023)

Volatile compounds comparison and mechanism exploration of non-smoked traditional Chinese bacon in Southwestern China and Eastern China - Han Wu; Zhifei He; Li Yang; Hongjun Li (Food Research International, 2023)

Standard environmental evaluation framework reveals environmental benefits of green light optimized speed advisory: A case study on plug-in hybrid electric vehicles - Ning Wei; Zhenyu Jia; Xiaoyang Zhao; Lin Wu; Yanjie Zhang; Jianfei Peng; Ting Wang; Zhiwen Yang; Qijun Zhang; Hongjun Mao (Journal of Cleaner Production, 2023)

Novel mesocellular silica foam supported poly(amidoxime-ethyleneimine) network for fast and highly efficient uranium extraction from seawater - Jiajia Yang; Yun Li; Tian Tian; Haitao Shi; Zia Ahmad; Ningbo Geng; Jing Jin; Yanqiang Huang; Haijun Zhang; Hongjun Fan; Jiping Chen (Chemical Engineering Journal, 2023)

Reveal the major factors controlling quinolone adsorption on mesoporous carbon: Batch experiment, DFT calculation, MD simulation, and machine learning modeling - Hongjun Zhao; Yitao Lyu; Jingrun Hu; Min Li; Huan Chen; Yi Jiang; Moran Tang; Yang Wu; Weiling Sun (Chemical Engineering Journal, 2023)

Interactions Between Humic Acid and the Forms and Bioavailability of Copper in Water - Hongwei Pan; Lili Shi; Xin Liu; Hongjun Lei; Guang Yang; Huiru Chen (Water, Air, & Soil Pollution, 2023)

Simultaneous adsorption and biodegradation of polychlorinated biphenyls using resuscitated strain Streptococcus sp. SPC0 immobilized in polyvinyl alcohol‑sodium alginate - Qihua Lin; Jiayan Ding; Yingying Yang; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Science of The Total Environment, 2023)

Impacts of heatwaves and cold spells on glaucoma in rural China: a national cross-sectional study - Ai Zhang; Qihua Wang; Xueli Yang; Yuanyuan Liu; Jiayu He; Anqi Shan; Naixiu Sun; Qianfeng Liu; Baoqun Yao; Fengchao Liang; Ze Yang; Xiaochang Yan; et al. (Environmental Science and Pollution Research, 2023)
China faces increasing health risks from climate change. The structure and function of the eye and vision were affected by extreme heat and cold. The study aimed to evaluate the impacts of heatwaves and cold spells on glaucoma. A national cross-sectional study of the Rural Epidemiology for Glaucoma (REG-China) was conducted in ten provinces of China, and 36,081 adults aged 40 years or more were included. Glaucoma signs were assessed via a standard examination. A total of 15 heatwave definitions, based on intensity (95th to 99th percentiles of temperature distribution) and duration (≥2 days, 3 days, and 4 days), were used to quantify heatwave effects, and 6 cold spell definitions were defined based on threshold temperature percentile (5th and 10th) and duration (3 days, 5 days, and 9 days). Multivariable-adjusted logistic regression models paired with interaction analysis were performed to investigate the impacts of heatwaves and cold spells on glaucoma, and the dose-response relationships were assessed using a restricted cubic spline (RCS) model. Subgroup analysis was conducted stratified by gender, age, smoking status, occupation, and family history of glaucoma. The overall prevalence of glaucoma was 2.1% (95% CI 1.94–2.25%). Higher heatwaves were significantly correlated with higher OR of glaucoma, with the OR (95% CI) ranging from 1.014 (1.009, 1.018) to 1.090 (1.065, 1.115) by different definitions. Glaucoma was affected by heatwaves more strongly than by cold spells. The effects of both heatwaves and cold spells were higher in males than females and in smokers than nonsmokers. These results of the present study evoked the attention of prospective research to elucidate the relationship between extreme temperatures and eye diseases.

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

Quality relationship between smoked and air-dried bacon of Sichuan-Chongqing in China: Free amino acids, volatile compounds, and microbial diversity - Li Yang; Hongjun Li; Han Wu; Chang Su; Zhifei He (Food Research International, 2023)

Dissimilatory manganese reduction facilitates synergistic cooperation of hydrolysis, acidogenesis, acetogenesis and methanogenesis via promoting microbial interaction during anaerobic digestion of waste activated sludge - Linli Wang; Yangyang Li; Xuesong Yi; Fei Yang; Dexin Wang; Hongjun Han (Environmental Research, 2023)

Multi-omics analysis reveals copper-induced growth inhibition mechanisms of earthworm (Eisenia fetida) - Yanliang Zhang; Jinqi Zhao; Na Sa; Chenyu Huang; Wenyu Yu; Tianxiao Ma; Hongjun Yang; Fang Ma; Siqi Sun; Chaochun Tang; Weiguo Sang (Environmental Pollution, 2023)

Dual-crosslinked hyaluronic acid hydrogel with self-healing capacity and enhanced mechanical properties - Mengfan Zhang; Xiao Chen; Kaidan Yang; Qi Dong; Hongjun Yang; Shaojin Gu; Weilin Xu; Yingshan Zhou (Carbohydrate Polymers, 2023)

Experimental Investigation on the Cyclic Shear Mechanical Characteristics and Dynamic Response of a Steel–Silt Interface in the Yellow River Delta - Peng Yu; Jie Dong; Yong Guan; Qing Wang; Shixiang Jia; Meijun Xu; Hongjun Liu; Qi Yang (Journal of Marine Science and Engineering, 2023)
The shear behavior and dynamic response of a steel–silt interface are significant for the safety and stability of offshore structures in the Yellow River Delta. A series of steel–silt interface cyclic shear tests under constant normal load conditions (CNL) were carried out to explore the effects of normal stress, shear amplitude, roughness, and water content on the interface shear strength, shear stiffness, and damping ratio using a large interface shear apparatus. The preliminary results showed that the amplitude of normal stress and shear amplitude affected the interface’s shear strength, stiffness, and damping ratio in a dominant manner. The roughness and water content were also crucial factors impacting the rule of shear strength, shear stiffness, and damping ratio, changing with the number of cycles. Under various scenarios, the steel–silt interface weakened distinctively, and the energy dissipation tended to be asymptotic with the cyclic shear.

Tunnel measurements reveal significant reduction in traffic-related light-absorbing aerosol emissions in China - Chung Song Ho; Jianfei Peng; Zongyan Lv; Bin Sun; Lei Yang; Jinsheng Zhang; Jiliang Guo; Qijun Zhang; Zhuofei Du; Hongjun Mao (Science of The Total Environment, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Emissions of air pollutants from non-road construction machinery in Beijing from 2015 to 2019 - Xueyao Li; Liu Yang; Yongteng Liu; Chongbo Zhang; Xiaohong Xu; Hongjun Mao; Taosheng Jin (Environmental Pollution, 2023)

Helical configuration channels boost performance in anion exchange membranes - Yang Zhang; Fan Zhang; Yiwen Chen; Lixuan Sun; Chengpeng Wei; Huaqing Zhang; Hongjun Zhang; Bangjiao Ye; Liang Wu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2023)

Microbial residues as the nexus transforming inorganic carbon to organic carbon in coastal saline soils - Pengshuai Shao; Tian Li; Kaikai Dong; Hongjun Yang; Jingkuan Sun (Soil Ecology Letters, 2022)

Study on Particle Size Distribution Characteristics in Urban Roadside Microenvironment Using an ELPI+ - Xiaozhen Fang; Lin Wu; Qijun Zhang; Jing Zhang; Zhiwen Yang; Chao Zou; Chao Ma; Yanjie Zhang; Hongjun Mao (Water, Air, & Soil Pollution, 2022)

Two-stage hybrid network for segmentation of COVID-19 pneumonia lesions in CT images: a multicenter study - Yaxin Shang; Zechen Wei; Hui Hui; Xiaohu Li; Liang Li; Yongqiang Yu; Ligong Lu; Li Li; Hongjun Li; Qi Yang; Meiyun Wang; Meixiao Zhan; et al. (Medical & Biological Engineering & Computing, 2022)

Response of soil carbon fractions and enzyme activities to mowing management on in a coastal wetland of the yellow river delta - Qian Cui; Hongjun Yang; Guangmei Wang; Jinzhao Ma; Lu Feng; Jingtao Liu (Frontiers in Marine Science, 2022)
Coastal wetlands are considered as important “blue carbon” sink, and mowing management induced by anthropogenic activities is anticipated to profoundly affect soil carbon stocks in coastal wetlands. However, the impacts of mowing management on soil organic carbon (SOC) and enzyme activities and the mechanisms responsible for associated changes in Phragmites australis wetland remain uncertain. We conducted a field mowing manipulation experiment [control (CK), mowing and returning straw in December (12MS), mowing and removing straw in December (12MR), mowing and returning straw in March (3MS), and mowing and removing straw in March (3MR)] in P. australis wetland of the Yellow River Delta and quantified their impacts on soil quality, SOC, SOC fractions, and enzyme activities. Results showed that mowing treatments led to overall increases in soil nutrients [total carbon (TC), total nitrogen (TN), total phosphorus (TP), NH 4 + , and NO 3 − ] and decreases in soil C/N ratio. The effects of mowing treatments on soil nutrient content were pronounced on topsoil than deep soil, and the maximum value of TC, TN, and TP reached in the 12MR treatment. Compared with CK, the 12MS, 12MR, 3MS, and 3MR treatments at 0–10 cm depth significantly enhanced SOC content by 8.78%, 32.9%, 16.5%, and 30.1%, respectively, but only the 3MS treatment enhanced SOC by 16.5% at 10–20 cm depth. Mowing treatments increased dissolved organic carbon (DOC), microbial biomass carbon (MBC), particulate organic carbon (POC), and labile organic carbon (LOC) and the contents of DOC, MBC, POC, and LOC decreased with soil depth. Mowing treatments stimulated the activities of sucrase and urease in topsoil, but only the 3MR treatment improved alkaline phosphatase activity in topsoil. Path analysis indicated that mowing management dominantly modulates SOC by changing sucrase activity, alkaline phosphatase activity, TN, TP, NH 4 + , NO 3 − , DOC, and LOC in 0–10 cm depth. However, SOC was significantly controlled by sucrase activity, urease activity, TC, TN, TP, LOC, and POC in 10–20 cm depth. Collectively, our results indicate that the continuous mowing management is beneficial to enhance soil quality and carbon storage capacity of P. australis wetlands, which will contribute to enhance carbon sequestration and sink capacity of coastal wetlands.

Daytime warming triggers tree growth decline in the Northern Hemisphere - Wenjing Tao; Kangshan Mao; Jiang He; Nicholas G. Smith; Yuxin Qiao; Jing Guo; Hongjun Yang; Wenzhi Wang; Jianquan Liu; Lei Chen (Global Change Biology, 2022)
Global warming has been linked to declines in tree growth. However, it is unclear how the asymmetry in daytime and nighttime warming influences this response. Here, we use 2947 residual tree‐ring width chronologies covering 32 species at 2493 sites, between 1901 and 2018, across the Northern Hemisphere, to analyze the effects of daytime and nighttime temperatures, precipitation, and drought stress on the radial growth of trees. We show that drought stress was primarily triggered by daytime rather than nighttime warming. The radial growth of trees was more sensitive to drought stress in warm regions than in cold regions, especially for angiosperms. Our study provides robust evidence that daytime warming is the primary driver of the observed declines in forest productivity related to drought stress and that daytime and nighttime warming should be considered separately when modelling forest–climate interactions and feedbacks in a future, warmer world.

PM2.5-PAHs and PM10-PAHs at roadside environment: levels, meteorological impact, source apportionment, and health risks - Qijun Zhang; Lei Yang; Yanjie Zhang; Xiaozhen Fang; Lin Wu; Hongjun Mao (Air Quality, Atmosphere & Health, 2022)

Multiple-Stage Mineralization in the Huayangchuan U−REE−Mo−Cu−Fe Ore Belt of the Qinling Orogen, Central China: Geological and Re−Os Geochronological Constraints - Hongjun Jiang; Chunsi Yang; Dequan Wang; Hui Zheng; Jie Li; Huayong Chen (Journal of Earth Science, 2022)
The Huayangchuan ore belt is located in the western segment of Xiaoqinling Orogen in the southern margin of the North China Craton (NCC), and hosts voluminous magmatism and significant U−REE−Mo−Cu−Fe polymetallic mineralization. However, geochronological framework of the various mineralization phases in this region is poorly understood. Here, we present new Re−Os isochron ages on magnetite from the Caotan Fe deposit (2 675 ± 410 Ma, MSWD = 0.55), and on pyrite from the Jialu REE deposit (2 127 ± 280 Ma, MSWD = 1.9) and Yuejiawa Cu deposit (418 ± 23 Ma, MSWD = 11.5), and Re−Os weighted average model age on pyrite from the Taoyuan Mo−U deposit (235 ± 14 Ma, MSWD = 0.17). These ages, combined with regional geology and mineralization ages from other deposits, suggest that mineralization in the Huayangchuan ore belt lasted from the Neoarchean to the Late Mesozoic. The mineralization corresponds to regional tectono-magmatic events, including the Neoar-chean alkali magmatism (REE mineralization), Paleoproterozoic plagioclase-amphibolite emplacement (Fe mineralization), Paleoproterozoic pegmatite magmatism (U mineralization), Paleozoic Shangdan oceanic slab subduction-related arc magmatism (Cu mineralization), Early Mesozoic Paleo-Tethys Ocean subduction-related arc magmatism (Mo−U mineralization), and Late Mesozoic Paleo-Pacific oceanic plate subduction direction change-related Mo(-Pb) mineralization. We proposed that the Huayang-chuan ore belt has undergone prolonged metallogenic evolution, and the magmatism and associated mineralization were controlled by regional geodynamic events.

Emission inventory and control policy for non-road construction machinery in Tianjin - Qijun Zhang; Ning Wei; Lei Yang; Xi Feng; Yanjie Zhang; Lin Wu; Hongjun Mao (Environmental Science and Pollution Research, 2022)

Combination of Polyethylene Glycol-Conjugated Urokinase Nanogels and Urokinase for Acute Ischemic Stroke Therapeutic Implications - Ding Nan; Haiqiang Jin; Di Yang; Weiwei Yu; Jingjing Jia; Zemou Yu; Hui Tan; Yongan Sun; Hongjun Hao; Xiaozhong Qu; Yining Huang (Translational Stroke Research, 2021)

Molecular characterization, expression, and apoptosis regulation of siva1 in protogynous hermaphrodite fish ricefield eel (Monopterus albus) - Zhi He; Faqiang Deng; Zhijun Ma; Qian Zhang; Jiayang He; Lijuan Ye; Hongjun Chen; Deying Yang; Liang He; Jie Luo; Taiming Yan (Fish Physiology and Biochemistry, 2021)

Stock Assessment of Hatchery-Released Clam Meretrix meretrix in an Estuary of China From the Perspectives of Population Ecology and Genetic Diversity - Anguo Zhang; Hongjun Li; Xiaolong Yang; Lili Wang; Yangchun Gao; Mingshan Song; Xiutang Yuan (Frontiers in Marine Science, 2021)
In this study, the release effects of the buried clam Meretrix meretrix in a northern estuary of China (Shuangtaizi Estuary) was assessed in terms of population ecology and genetic variability by using longer-term monitoring data from 2011 (used as the baseline data) to 2018. A total of 2.4 × 10 8 hatchery juveniles were released from 2012 to 2014, and follow-up monitoring survey of the growth, distribution, density, and biomass of M. meretrix population was carried out. Results showed a temporary spike in the population of M. meretrix , and the population underwent considerable year-to-year fluctuations in total abundance and biomass. Meanwhile, the age structure of the populations from 2011 to 2018 is still an unstable expanding type. Genetic analysis based on 10 polymorphic microsatellite markers revealed no significant genetic differentiation and weak genetic structures between years but higher genetic diversities in 2014–2018 than in the initial period (2013) of stock restoration. Our study suggests that effective policies for management and conservation to restore M. meretrix population by local governments are still needed in the long run.

Genomic selection to introgress exotic maize germplasm into elite maize in China to improve kernel dehydration rate - Hongjun Yong; Nan Wang; Xiaojun Yang; Fengyi Zhang; Juan Tang; Zhiyuan Yang; Xinzhe Zhao; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; et al. (Euphytica, 2021)

Oxidative Stress and Trace Elements in Pulmonary Tuberculosis Patients During 6 Months Anti-tuberculosis Treatment - Chaoqun Qi; Hongjun Wang; Zhaoying Liu; Haibo Yang (Biological Trace Element Research, 2021)

Distribution and Assessment of Cr, Pb, Ni and Cd in Topsoil of the Modern Yellow River Delta, China - Hongjun Yang; Jingkuan Sun; Jiangbao Xia; Zhanyong Fu; Shuai Cheng; Tian Li; Pengshuai Shao; Kaikai Dong; Jinzhao Ma; Lu Feng (Wetlands, 2021)

Potential N mineralization and availability to maize in black soils in response to soil fertility improvement in Northeast China - HaiMei Fu; YingHua Duan; Ping Zhu; HongJun Gao; MingGang Xu; XiaoMei Yang (Journal of Soils and Sediments, 2021)

Comparative analysis of H3K4 and H3K27 trimethylations in two contrasting Tibetan hulless barely varieties on powdery mildew infection - Sang Zha; Chunbao Yang; Xingquan Zeng; Zeqing Li; Yulin Wang; Hongjun Yuan; Mingzhai Yu; Qijun Xu (Journal of Plant Pathology, 2021)

Bilinear neural network with 3-D attention for brain decoding of motor imagery movements from the human EEG - Chen-Chen Fan; Hongjun Yang; Zeng-Guang Hou; Zhen-Liang Ni; Sheng Chen; Zhijie Fang (Cognitive Neurodynamics, 2021)

Optimization of porcine embryonic germ cell culture system - Yang Li; Yu Qiao; Fei Li; Hongjun Wang; Xiao Dong (In Vitro Cellular & Developmental Biology - Animal, 2020)

Geochemistry and Petrogenesis of Volcanic Rocks from the Continent-Ocean Transition Zone in Northern South China Sea and Their Tectonic Implications - Yue Xu; Yaoming Yang; Hongjun Yu; Wei Gao; Xiangxing Gao; Baohua Liu; Xu Tian; Jichao Yang; Wenquan Zhang (Journal of Ocean University of China, 2020)

A new permeability predictive model based on NMR data for sandstone reservoirs - Hongjun Xu; Changxi Li; Yiren Fan; Falong Hu; Jun Yu; Jinyu Zhou; Changxue Wang; Chunmei Yang (Arabian Journal of Geosciences, 2020)

Phylogenetic analysis of the whole genome sequence of a dog lineage rabies virus detected from cattle in eastern China, 2019 - Kaihui Cheng; Huimeng Chu; Yachu Ren; Xiaoli Xie; Zhijun Yu; Hongjun Yang (Brazilian Journal of Microbiology, 2020)

Comprehensive Investigation and Assessment of Nutrient and Heavy Metal Contamination in the Surface Water of Coastal Bohai Sea in China - Heshan Lin; Hongjun Li; Xiaolong Yang; Zizhou Xu; Yindong Tong; Xingguang Yu (Journal of Ocean University of China, 2020)

Salvianolic acid A attenuated myocardial infarction–induced apoptosis and inflammation by activating Trx - Rui Zhou; Jinhuan Gao; Changpei Xiang; Zhenming Liu; Yi Zhang; Jingjing Zhang; Hongjun Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Magnetic properties indicate the sources of hadal sediments in the Yap Trench, northwest Pacific Ocean - Yu Chen; Jichao Yang; Olusegun A. Dada; Yaomin Yang; Zhen Lin; Zhen Cui; Yue Xu; Hongjun Yu; Baohua Liu (Journal of Oceanology and Limnology, 2020)

Effect of five modified mass selection cycles on combining ability in two Chinese maize populations - Hongjun Yong; Juan Tang; Xinzhe Zhao; Fengyi Zhang; Zhiyuan Yang; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Jienan Han; Bo Peng; et al. (Euphytica, 2020)

Fine mapping of the wheat powdery mildew resistance gene Pm52 using comparative genomics analysis and the Chinese Spring reference genomic sequence - Peipei Wu; Jinghuang Hu; Jingwei Zou; Dan Qiu; Yunfeng Qu; Yahui Li; Teng Li; Hongjun Zhang; Li Yang; Hongwei Liu; Yang Zhou; Zhongjun Zhang; et al. (Theoretical and Applied Genetics, 2019)

Breeding potential of inbred lines derived from five maize (Zea mays L.) populations - Hongjun Yong; Fengyi Zhang; Juan Tang; Zhiyuan Yang; Xinzhe Zhao; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Xinhai Li (Euphytica, 2019)

Threshold effect of the groundwater depth on the photosynthetic efficiency of Tamarix chinensis in the Yellow River Delta - Jiangbao Xia; Jiayun Ren; Ximei Zhao; Fengjuan Zhao; Hongjun Yang; Junhua Liu (Plant and Soil, 2018)

Bearing capacity of offshore umbrella suction anchor foundation in silty soil under varying loading modes - Qi Yang; Guanglai Pan; Hongjun Liu; Quandi Wang (Marine Georesources & Geotechnology, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

Geochemistry of pyrite and chalcopyrite from an active black smoker in 49.6°E Southwest Indian Ridge - Bo Yuan; Yaomin Yang; Hongjun Yu; Yuexia Zhao; Qingfeng Ding; Jichao Yang; Xin Tang (Marine Geophysical Research, 2018)

The impact of modern plant breeding on dominant Chinese wheat cultivars (Triticum aestivum L.) revealed by SSR and functional markers - Lingzhi Meng; Chao Xiang; Hongwei Liu; Li Yang; Chunyan Mai; Liqiang Yu; Yunliang Wei; Hongjie Li; Hongjun Zhang; Yang Zhou (Genetic Resources and Crop Evolution, 2018)

The responses of two native plant species to soil petroleum contamination in the Yellow River Delta, China - Wenjun Xie; Yanpeng Zhang; Rui Li; Hongjun Yang; Tao Wu; Liping Zhao; Zhaohua Lu (Environmental Science and Pollution Research, 2017)

The Impact of Impoundment on Mercury Bioaccumulation in Fish Downstream from a Newly Constructed Reservoir, Wujiang River, Southwest China - Sixin Li; Lianfeng Zhou; Jianbo Chang; Zhi Yang; Juxiang Hu; Wang Hongjun (Archives of Environmental Contamination and Toxicology, 2017)

Alternative reverse genetics system for influenza viruses based on a synthesized swine 45S rRNA promoter - Kai Wang; Qi Huang; Zhiwei Yang; Kezong Qi; Hongmei Liu; Hongjun Chen (Virus Genes, 2017)

De novo assembly, gene annotation, and molecular marker development using Illumina paired-end transcriptome sequencing in the clam Saxidomus purpuratus - Hongjun Li; Min Liu; Sheng Ye; Feng Yang (Genes & Genomics, 2017)

Efficacy and safety of quetiapine extended release monotherapy in bipolar depression: a multi-center, randomized, double-blind, placebo-controlled trial - Huafang Li; Niufan Gu; Hongyan Zhang; Gang Wang; Qingrong Tan; Fude Yang; Yuping Ning; Honggeng Zhang; Zheng Lu; Xiufeng Xu; Jianguo Shi; Chengge Gao; et al. (Psychopharmacology, 2016)

Optimization of culture conditions for porcine embryonic germ cells - Xiao Dong; Yang Li; Hongjun Wang (In Vitro Cellular & Developmental Biology - Animal, 2016)

In vivo construction of tissue-engineered cartilage using adipose-derived stem cells and bioreactor technology - Hongjun Kang; Shibi Lu; Jiang Peng; Qiang Yang; Shuyun Liu; Li Zhang; Jingxiang Huang; Xiang Sui; Bin Zhao; Aiyuan Wang; Wenjing Xu; Quanyi Guo; et al. (Cell and Tissue Banking, 2015)

Isolation and characterization of microsatellite loci from Gasterophilus pecorum (Diptera: Gasterophilidae) - Fang Cheng; Jianmei Yang; Dong Zhang; Defu Hu; Hongjun Chu; Jie Cao; Feng Jiang; Lan Bu; Kai Li (Conservation Genetics Resources, 2014)

Relationships between the West Asian subtropical westerly jet and summer precipitation in northern Xinjiang - Yong Zhao; MinZhong Wang; AnNing Huang; HongJun Li; Wen Huo; Qing Yang (Theoretical and Applied Climatology, 2014)

Distribution of phthalate esters in topsoil: a case study in the Yellow River Delta, China - Yang Hongjun; Xie Wenjun; Liu Qing; Liu Jingtao; Yu Hongwen; Lu Zhaohua (Environmental Monitoring and Assessment, 2013)

Short-term impact of reservoir impoundment on the patterns of mercury distribution in a subtropical aquatic ecosystem, Wujiang River, southwest China - Sixin Li; Lianfeng Zhou; Hongjun Wang; Meihua Xiong; Zhi Yang; Juxiang Hu; Youguang Liang; Jianbo Chang (Environmental Science and Pollution Research, 2013)

The Alteration of MiR-222 and Its Target Genes in Nickel-Induced Tumor - Jing Zhang; Yang Zhou; Lin Ma; Shunquan Huang; Ruijin Wang; Rongrong Gao; Youjun Wu; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2013)

Isolation and Characterization of a Novel Noncoding RNA from Nickel-Induced Lung Cancer - Jing Zhang; Yang Zhou; Youjun Wu; Lin Ma; Yingying Fan; Xuan Kang; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2012)

Major histocompatibility complex class IIA and IIB genes of the spotted halibut Verasper variegatus: genomic structure, molecular polymorphism, and expression analysis - Hongjun Li; Lianxin Jiang; Jiabo Han; Hao Su; Qing Yang; Chongbo He (Fish Physiology and Biochemistry, 2011)

Identification of Differentially Expressed Genes in Lung Tissues of Nickel-Exposed Rats Using Suppression Subtractive Hybridization - Jing Zhang; Jun Zhang; Yingying Fan; Lihong Liu; Mengjie Li; Yang Zhou; Zhihua Shao; Hongjun Shi; Ying Wang (Biological Trace Element Research, 2011)

Molecular analysis and recombinant expression of bovine neutrophil β-defensin 12 and its antimicrobial activity - Jianming Wu; Changfa Wang; Hongbin He; Guixue Hu; Hongjun Yang; Yundong Gao; Jifeng Zhong (Molecular Biology Reports, 2011)

1H and 13C NMR spectroscopic studies of the ferriheme resonances of three low-spin complexes of wild-type nitrophorin 2 and nitrophorin 2(V24E) as a function of pH - Fei Yang; Markus Knipp; Tatiana K. Shokhireva; Robert E. Berry; Hongjun Zhang; F. Ann Walker (JBIC Journal of Biological Inorganic Chemistry, 2009)

Characteristics and causes of the preconsolidation stress of soils in the Yellow River Delta - Xiujuan Yang; Yonggang Jia; Hongjun Liu; Hongxian Shan (Journal of Ocean University of China, 2009)

Association of North Atlantic Oscillations with Aksu River runoff in China - Hongjun Li; Zhihong Jiang; Qing Yang (Journal of Geographical Sciences, 2009)